2022
DOI: 10.1021/acsomega.2c02243
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Routine Chemical Constituents of Tobacco Based on Thermogravimetric Analysis

Abstract: As the most basic indexes to evaluate the quality of tobacco, the contents of routine chemical constituents in tobacco are mainly detected by continuous-flow analysis at present. However, this method suffers from complex operation, time consumption, and environmental pollution. Thus, it is necessary to establish a rapid accurate detection method. Herein, different from the ongoing research studies that mainly chose near-infrared spectroscopy as the information source for quantitative analysis of chemical compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…In contrast, flue- and sun-cured tobacco leaves contain higher sugar levels as the metabolising enzymes are rapidly inactivated at the relatively high temperatures employed during this curing [ 52 ]. The total nitrogen, total alkaloid, chloride and potassium contents were 1.48–2.30, 1.56–3.08, 0.20–0.93 and 1.04–1.88 %, respectively, which is in agreement with those of a previous study, wherein Peng et al [ 45 ] found that the total nitrogen, total alkaloids, chloride, and potassium contents in tobacco were 1.63–2.42, 1.48–3.27, 0.07–1.10 and 1.36–2.89 %, respectively.
Fig.
…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In contrast, flue- and sun-cured tobacco leaves contain higher sugar levels as the metabolising enzymes are rapidly inactivated at the relatively high temperatures employed during this curing [ 52 ]. The total nitrogen, total alkaloid, chloride and potassium contents were 1.48–2.30, 1.56–3.08, 0.20–0.93 and 1.04–1.88 %, respectively, which is in agreement with those of a previous study, wherein Peng et al [ 45 ] found that the total nitrogen, total alkaloids, chloride, and potassium contents in tobacco were 1.63–2.42, 1.48–3.27, 0.07–1.10 and 1.36–2.89 %, respectively.
Fig.
…”
Section: Resultssupporting
confidence: 92%
“…The routine chemical components in FCT leaves including total/reducing sugars, total alkaloid, total nitrogen, potassium and chloride were determined using a continuous flow analyser (SAN++, Skalar, Holland) according to Peng et al [ 45 ]. And total sugar-nicotine ratio, total nitrogen-nicotine ratio and potassium-chloride ratio are extrapolated values.…”
Section: Methodsmentioning
confidence: 99%
“…showed that “prolonged storage (24 hours) in methanol, isopropanol or ethanol removed 10–12 moles of water from AFm phases, where isopropanol and ethanol can remove only 1∼2 moles of water from AFt phases and methanol destroys the morphology of AFt phases.” 191 Despite these challenges, TGA is not time‐consuming, easy to execute, and suitable for qualitative and, in some cases (where decomposition peaks do not overlap with other peaks), quantitative analyses for both crystalline and amorphous hydrates. Future research can be initiated by adding chemometric analysis to understand the stepwise decomposition behavior of AFt in cementitious systems from TGA data 192 . Another approach is to combine TGA–DSC (differential scanning calorimetry) to understand the de‐/rehydration of AFt phases in a ternary cementitious system 193 .…”
Section: Discussionmentioning
confidence: 99%
“…Future research can be initiated by adding chemometric analysis to understand the stepwise decomposition behavior of AFt in cementitious systems from TGA data. 192 Another approach is to combine TGA-DSC (differential scanning calorimetry) to understand the de-/rehydration of AFt phases in a ternary cementitious system. 193 This will also help to modify the thermodynamic data to understand the temperature and water vapor pressure-dependent behavior of ettringite and meta ettringite in an AFt-based system.…”
Section: Discussionmentioning
confidence: 99%